Efficacy of Parquetina nigrescens Leaf Extract on Growth Performance and Gastrointestinal Response of Japanese Quails - Akintunde, Adeyinka Oye; Ndubuisi-Ogbonna, Lois Chidinma; Ogundipe, Oluwaseyi Esther; Akeju, Samuel Inioluwa; Akinboye, Olufunso Emmanuel; Adewole, Oluwaseun Adetayo; Animashaun, Rufus Olusegun (Jurnal Medik Veteriner, 2025)
Japanese quail has the potential to complement the gap in the protein need of Nigerians. This study aimed to evaluate the effects of varying inclusion levels of Parquetina nigrescens leaf extract (PNLE) on the growth performance, gastrointestinal response, and plasma response of Japanese quails (Coturnix coturnix japonica). Fresh leaves of P. nigrescens were harvested. Two-hundred day old of unsexed Japanese quails were weighed and randomly allocated to 5 dietary treatment groups with forty birds at 4 replicates of 10 chicks, respectively. The leaf was obtained by harvesting and blending the leaves, using 50 g of leaves in 1000 mL of water. The treatment were as follows: (T1) which is the control did not receive any PNLE, T2, T3, T4 and T5 administered 0.2, 0.4, 0.6, 0.8 mL of PNLE per 500 mL of water, respectively, for 6 week of experiment. Feed and water were provided ad libitum and mortality was recorded as it occurred. Parameters measured were performance (feed intake, weight gain, feed conversion ratio (FCR) and gastrointestinal response (Internal organ of GIT and morphometrics). All data were subjected to analysis of variance using Duncan’s multiple range test in SAS (2010) where p value < 0.005 was considered to be statistically significant. For performance, the results showed that the administration of PNLE did not have significant influence (p > 0.05) on all the parameters in the starter and finisher phases. It was observed that when all the parameters were put together without considering the phases, all the parameters considered were not significant (p > 0.05) except feed conversion ratio (FCR) with the highest value being in T1 (5.041) and the lowest value being T4 (3.183). For the gastrointestinal response parameters, the inclusion of PNLE had significant effect (p < 0.05) on crop pH, proventriculus temperature, proventriculus pH, gizzard weight, gizzard temperature, relative gizzard weight, jejunum length and ileum temperature. It was concluded that the inclusion of PNLE had no detrimental effect on growth performance, gastrointestinal response and plasma of Japanese quail, hence it can be used up to 0.4 mL into 500 mL of water.